Food safety and hygiene knowledge, attitudes and practices in street restaurants selling chicken in Ouagadougou, Burkina Faso - Gemeda, Biruk A.; Dione, Michel M.; Ilboudo, Guy S.; Assefa, Ayalew; Lallogo, Valerie; Grace, Delia; Knight-Jones, Theodore J.D. (Frontiers Media, 2024)
Introduction: Chicken is the most commonly consumed animal source food in street restaurants in Burkina Faso. In most of these restaurants, slaughtering, processing, and cooking practices are carried out under poor hygienic conditions.